2007
DOI: 10.1007/s10517-007-0174-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of psychoemotional status of rats after brain injury and systemic transplantation of mesenchymal stem cells

Abstract: We studied the effects of systemic transplantation of mesenchymal stem cells obtained after culturing of autologous bone marrow on psychophysiological status of Wistar rats after diffuse brain trauma. Two months after systemic injection of mesenchymal stem cells we observed a decrease in manifestations of emotional behavioral reactions (anxiety and excitability) and shortening of the time of realization of drinking behavior in a T-maze. A significant positive effect of systemic transfusion of mesenchymal stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…A previous study suggested that MSCs increase production of nerve growth factor and brain-derived neurotrophic factor (BDNF) and induce repair of the central nervous system (4). The results of preclinical studies have suggested the usefulness of MSCs in TBI (32,33), but imaging methods have shown little evidence of a therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that MSCs increase production of nerve growth factor and brain-derived neurotrophic factor (BDNF) and induce repair of the central nervous system (4). The results of preclinical studies have suggested the usefulness of MSCs in TBI (32,33), but imaging methods have shown little evidence of a therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%